2002
DOI: 10.1097/00006676-200211000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Unresectable, Locally Advanced Pancreatic Adenocarcinoma with Combined Radiochemotherapy with 5-Fluorouracil and Cisplatin

Abstract: This RCT regimen had a good impact on clinical benefit in locally advanced pancreatic carcinoma, without severe side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…This is comparable to results published in international literature in which survival ranges from 9 to 14 months [3,7,8,9,10,11,12, 14,19,20,21,22,23,30,31,32,33,34,35,36,37]. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is comparable to results published in international literature in which survival ranges from 9 to 14 months [3,7,8,9,10,11,12, 14,19,20,21,22,23,30,31,32,33,34,35,36,37]. …”
Section: Discussionsupporting
confidence: 89%
“…In this study 26% of patients showed a response and 16% had stable disease after 2 months which is again comparable to international results [3,7,8,9, 11, 12, 19, 21,30,31,32,33,34,35]. However, only 2 patients (5%) of the total group underwent a radical (R0) resection.…”
Section: Discussionsupporting
confidence: 88%
“…We have also learned that weekly doses of gemcitabine of up to 250-300 mg/m 2 can be given without intolerable toxicity in parallel to radiotherapy [48][49][50][51][52][53][54][55][56][57][58][59]. Paclitaxel, oxaliplatin and cisplatin are potent radiosensitizers, which are tested in combination with radiotherapy for pancreatic cancer [53,[60][61][62][63][64]. Inoperable tumors of the pancreas are ideal targets for novel irradiation techniques like intensity-modulated radiotherapy used in conjunction with image guidance, e.g.…”
Section: Future Studiesmentioning
confidence: 99%
“…Patient survival of this devastating disease is bleak with less than 5% of patients surviving 5 years after the time of diagnosis (Greenlee et al, 2000). The current treatment includes a combination of surgery, chemotherapy, and radiation without any major improvement in survival (Azria et al, 2002). Over 10 years ago, it was hypothesised that TNFa could increase tumour response to radiation through stimulation of the host antitumour immune responses, direct tumour-cell kill, or through the increase in tumour-cell sensitivity to radiation (Sersa et al, 1988;Hallahan et al, 1990;Gridley et al, 1994a, b;Kimura et al, 1999;Azria et al, 2003a).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, at the time of diagnosis, the majority of patients (80 -90%) have locally or metastatic inoperable tumours. Radiation therapy (RT) alone or in combination with chemotherapy showed modest efficacy in local control and palliation (Andre et al, 2000;Kornek et al, 2000;Azria et al, 2002). Despite these intensive efforts to improve the efficacy of conventional therapy, no satisfactory progress in dealing with this cancer has been made.…”
mentioning
confidence: 99%